Air pollution influences epiphytic lichen diversity in the Northeast of Thailand - Dathong,W. (Trans Tech Publications, 2015)
© (2014) Trans Tech Publications, Switzerland. This work aimed to investigate epiphytic lichens on mango trees (Mangifera indica L.) in the municipality habitats of the Northeast of Thailand based on the Verein Deutscher Ingenieure protocol and define the factors that influence their diversity. Ninety-one taxa were observed, 21 of them are macrolichens, 87 species found outside municipality and 70 species found inside municipality. The factors that most affected epiphytic lichen diversity were tree circumference, days of rainfall, bark pH, area surrounding and annual rainfall and negatively affected by population size, temperature, and distance from road. This work concluded that traffic density and human population size reduce air quality and influenced epiphytic diversity in the municipal habitats in the Northeast of Thailand, and lichens are bioindicators of air pollution in this region.